2022
DOI: 10.1039/d2ta01065h
|View full text |Cite
|
Sign up to set email alerts
|

High-density active site COFs with a flower-like morphology for energy storage applications

Abstract: Redox-active covalent organic frameworks (COFs) are an emerging class of energy storage materials with notably abundant active sites, well-defined 1D channels and highly surface areas. However, during the process of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…It can be observed that there are a pair of redox peaks at 0 to −0.2 V. This peak originates from the high-density quinone carbonyl sites in the COF skeleton and the DAAQ pillars. 18,49 The difference between the oxidation peak and the reduction peak potential is an important According to the calculation, the areal specific capacitance of AC-COFs at 1 mA cm −2 is 1034 mF cm −2 (397.7 F g −1 ), which is almost 230 times that of CC and 50 times that of DAAQ-Tp COFs. This value is better than most recently reported flexible electrodes used in supercapacitors (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…It can be observed that there are a pair of redox peaks at 0 to −0.2 V. This peak originates from the high-density quinone carbonyl sites in the COF skeleton and the DAAQ pillars. 18,49 The difference between the oxidation peak and the reduction peak potential is an important According to the calculation, the areal specific capacitance of AC-COFs at 1 mA cm −2 is 1034 mF cm −2 (397.7 F g −1 ), which is almost 230 times that of CC and 50 times that of DAAQ-Tp COFs. This value is better than most recently reported flexible electrodes used in supercapacitors (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…In addition, a significant signal was shown near 184 ppm, corresponding to carbonyl carbon. 18 In the thermal gravimetric analysis (TGA, Figure S13) under air, the pristine CC has no significant weight loss at 800 °C. The weight loss of modified AC, AC-DAAQ, CC/COFs, and AC-COFs at 25−200 °C is due to the evaporation of surfaceadsorbed water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations